Hubungan Job Search Self-Efficacy dengan Career Adaptability - Riesca Monica Hartono; William Gunawan (Fakultas Psikologi Universitas Pancasila, 2017)
There are many changes in the workforce in this recent years. Graduate students who want to join the workforce should have high career adaptability and job search self-efficacy, to enable them to be success. The aim of this research was to found out the relationship between students job search self-efficacy (JSSE) with career adaptability (CA) in University (N=82) with quantitative approach. Researcher using career adaptability scale (Savickas, 2012) and job search self-efficacy (Wanberg, et.al, 2010) and then analyzed it with correlation methods. A Focused Group Discussion was given to explore more findings. The reliability score from JSSE is 0.826 and CA is 0.931. The JSSE validity score was 0.435-0.817 and CA validity score was 0.33-0.83. The results showed that there was a correlation between career adaptability and job search self-efficacy (r=0.598; p<0.05).